Continuous and Discrete Time Approaches to a Maximization Problem - Telser, L. G.; Graves, R. L. (Review of Economic Studies, 1968)
Journal Article Continuous and Discrete Time Approaches to a Maximization Problem Get access L. G. Telser, L. G. Telser University of Chicago Search for other works by this author on: Oxford Academic Google Scholar R. L. Graves R. L. Graves University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 3, July 1968, Pages 307–325, https://doi.org/10.2307/2296664 Published: 01 July 1968